Pan : from the papers of Lieutenant Thomas Glahn - Hamsun, Knut, 1859-1952.; Lyngstad, Sverre (New York, N.Y. : Penguin Books, 1998)
First published in 1894, Knut Hamsun's PAN recounts Thomas Glahn's retrospective narrative of his life and adventures in the Norwegian woods. PAN provides a lyrical, yet disturbing, analysis of love and the recesses of the psyche. This superb new translation restores the power and virtuosity of Hamsun's original and includes an informative Introduction.
Includes bibliographical references (p. 127-131).